2-Bromo[6]helicene as a Key Intermediate for [6]Helicene Functionalization - Jakubec, Martin; Beránek, Tomáš; Jakubík, Pavel; Sýkora, Jan; Žádný, Jaroslav; Církva, Vladimír; Storch, Jan (The Journal of organic chemistry, 2018)
The synthesis of 2-bromo[6]helicene was revised and improved up to 51% yield. Its reactivity was thoroughly investigated, and a library of 17 different carbon, boron, nitrogen, phosphorus, oxygen and sulfur substituted derivatives was prepared. The racemization barrier for 2-bromo[6]helicene was determined, and the usage of enantiomers in the synthesis of optically pure helicenes was rationalized. The three most energy-demanding reactions using enantiomerically pure 2-bromo[6]helicene were tested in order to confirm the predicted enantiomeric excess.